Internet-Based Teaching and Experiment System for Control Engineering Course - Min Wu; Jin-Hua She; Gui-Xiu Zeng; Ohyama, Y. (IEEE transactions on industrial electronics (1982), 2008)
e-Learning engineering courses with online experiments are attracting a great deal of attention because of the flexibility they provide in both teaching and learning. This paper has described an Internet-based teaching and experiment system for control engineering (ITESCE) that provides students with online course material, a simulator, an online control experiment using an arm robot, and the ability to store and search simulation and experimental results. To implement the functions required by the course and to facilitate connection to the Internet, the ITESCE is based on a standard browser/server architecture with three layers and employs multithreading, Java applets, and Java database connectivity. Background control subsystems handle the real-time control of experiments, and a network server handles communication with clients and with background control subsystems. A database stores simulation and experimental results. The course covers a variety of control methods, and students can try them out through online simulations and experiments. To enhance realism, a Web camera takes a video of an experiment and streams it to a student's PC in real time.